2002
DOI: 10.1002/ird.54
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DRAINMOD‐S for simulating water table management under semi‐arid conditions

Abstract: The water table management simulation model, DRAINMOD-S, was evaluated under semi-arid conditions using field data from the Maruit experimental field in the western delta of Egypt for three cropping seasons; maize 1999, wheat 1999/2000 and maize 2000. Two water table management systems (conventional drainage (FD) and controlled drainage (CD)) were applied in the study area. The recorded data included daily ground water table depths, drain outflows during flow events, soil salinity to depth of 1.20 m from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 6 publications
(3 reference statements)
3
23
0
Order By: Relevance
“…Previous evaluation of the DRAINMOD model under different soil and climatic conditions indicated that the values of average absolute deviation and standard error of estimate for (Wahba et al, 2002). Based on the results obtained and considering the methods of filed measurement, spatial variability of field data, and the approximation of model inputs, it can be concluded that the model provides reasonable approximation of water table trends under these conditions in Southeastern Australia.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous evaluation of the DRAINMOD model under different soil and climatic conditions indicated that the values of average absolute deviation and standard error of estimate for (Wahba et al, 2002). Based on the results obtained and considering the methods of filed measurement, spatial variability of field data, and the approximation of model inputs, it can be concluded that the model provides reasonable approximation of water table trends under these conditions in Southeastern Australia.…”
Section: Resultsmentioning
confidence: 84%
“…For the conditions of the Western Delta of Egypt, the model simulated the total outflows with an average absolute deviation from 18 to 75 mm (Wahba et al, 2002). The average absolute deviation and the standard error are statistical measures for the difference between observed and simulated values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model showed the potential for longterm simulation and planning of groundwater table management under semi-arid conditions of the Western Delta of Egypt (Wahba et al, 2002).…”
Section: Water Saving By Management Of Subsurface Drainage Applicatiomentioning
confidence: 99%
“…From these results, it could be concluded that in spite of small deviations at some points, an excellent visual match could be obtained between the observed and simulated values. The deviations between predicated and measured data revealed that AD for the groundwater table depth was 0.18 m while SE was 0.24 m. Evaluation of this and the other model under different soil and climate conditions previously indicated that the values of AD and SD for groundwater table depth ranged from 0.11 to 0.16 m and from 0.13 to 0.19 m respectively (Wahba et al ., ), from 0.14 to 0.24 m and from 0.15 to 0.30 m respectively (Gupta et al ., ), from 0.04 to 0.20 m and from 0.06 to 0.24 m respectively (Chang et al ., ; Skaggs, ; Abdel‐Dayem and Skaggs, ) and 0.13 and 0.15 respectively (Hirekhan et al ., ). The AD and SE were 1.07 and 2.15 mm day ‐1 respectively for the drainage discharge rate, and 7.8 and 9.6 mm respectively for the cumulative drainage discharge.…”
Section: Resultsmentioning
confidence: 99%